Crk adaptors negatively regulate actin polymerization in pedestals formed by enteropathogenic Escherichia coli (EPEC) by binding to Tir effector. - Elvira Nieto-Pelegrin; Eugenia Meiler; José Manuel Martín-Villa; María Benito-León; Narcisa Martinez-Quiles (PLoS Pathogens)
Infections by enteropathogenic Escherichia coli (EPEC) cause diarrhea linked to high infant mortality in developing countries. EPEC adheres to epithelial cells and induces the formation of actin pedestals. Actin polymerization is driven fundamentally through signaling mediated by Tir bacterial effector protein, which inserts in the plasma membrane of the infected cell. Tir binds Nck adaptor proteins, which in turn recruit and activate N-WASP, a ubiquitous member of the Wiskott-Aldrich syndrome family of proteins. N-WASP activates the Arp2/3 complex to promote actin polymerization. Other proteins aside from components of the Tir-Nck-N-WASP pathway are recruited to the pedestals but their functions are unknown. Here we investigate the function of two alternatively spliced isoforms of Crk adaptors (CrkI/II) and the paralog protein CrkL during pedestal formation by EPEC. We found that the Crk isoforms act as redundant inhibitors of pedestal formation. The SH2 domain of CrkII and CrkL binds to phosphorylated tyrosine 474 of Tir and competes with Nck to bind Tir, preventing its recruitment to pedestals and thereby inhibiting actin polymerization. EPEC infection induces phosphorylation of the major regulatory tyrosine in CrkII and CrkL, possibly preventing the SH2 domain of these proteins from interacting with Tir. Phosphorylated CrkII and CrkL proteins localize specifically to the plasma membrane in contact with EPEC. Our study uncovers a novel role for Crk adaptors at pedestals, opening a new perspective in how these oncoproteins regulate actin polymerization.